Role of active and passive surveillance in early case detection and prevention of disease spread in COVID-19 pandemic: our experience - Pradeep, Kumar; Samundeswari, Gopinathan; Niranjan, Rajasekar; Dorthy, Velayutham; Malar, Ilango; Velavan, Anandan; Konduru, Rajesh Kumar; Kumar, Prahan; Purty, Anil J. (International Journal of Research in Medical Sciences, 2022)
Background: Strong surveillance systems which include both active and passive surveillance are the important steps to halt a disease outbreak by early case detection and management, which helps in breaking the chain of transmission. The main aim of this article is to share our experience regarding the active and passive surveillance done during COVID 19 spread in the year 2021. Methods: The early case detection of COVID 19 cases through active and passive surveillance was slightly different from the usual methods that are carried out for regular known communicable diseases. Active surveillance was done round the clock by screening of all vehicles entering the union-territory of Puducherry and by house-to-house survey. Passive surveillance was carried out by screening of various symptomatic patients attending to hospitals which needed motivation of health personnel as well as awareness among the general public. Results: Out of 12 Govt. PHCs (3,30,000population) where active and passive surveillance was conducted, the total number of individuals referred to designated COVID centre by active and passive surveillance is 30 and 110 respectively for COVID testing and further management. Conclusions: Active and Passive surveillance plays a major role in early case detection and prevention of disease spread in COVID-19 pandemic.